Political Expenditure Cycle in V4 Countries - Lenka Malicka (Montenegrin Journal of Economics)
Public expenditure subjects to government and its volume and structure is influenced by decisions of government according to activities and fiscal policies realized. Political expenditure cycles could also act as one of potential public expenditure determinant and could influence the public expenditure volume and structure. The paper examines whether the political expenditure cycle is present in V4 countries at the central level of government considering the opportunistic approach. Variance of central government expenditure indicates the presence of changes in the central government total expenditure and in its sub-categories defined according to government functions, while the analysis of their dynamics in connection with parliamentary election brings only vague results. After, the OLS model is estimated for each V4 country for the period 1995-2015. Results of estimations present certain statistically significant impact of election period on the central government total expenditure. As the monitored time-series cover the period of the financial crisis, models were tested for the structural break. Augmented regressions were re-estimated. Results point to cases, when election variables meet the hypothesis about the opportunistic behaviour of central government. Additionally, prevalent part of results shows opposite behaviour of the central government before and after the financial crisis. However, observed results do not allow generalizing the opportunistic model to all V4 post-communist countries, because statistically significant opposite effects of tested hypothesis are also observed..